Huge Subserosal Leiomyoma fed by serpentine omental blood vessels - Maskey, Suvana; Gurung, Geeta; Baral, Josie; Paudyal, Pooja (Nepal Journal of Obstetrics and Gynaecology, 2020)
Leiomyoma is considered the most common benign tumor of genital tract with variable presentation and diverse operative findings. We are presenting a case of asymptomatic huge subserosal pedunculated leiomyoma in a 37 years unmarried nullipara lady diagnosed as highly vascular abdominopelvic mass preoperatively as suggested by imaging studies but of uncertain origin, imposing surgical challenge due to diagnostic dilemma and its vascularity. Laparotomy revealed solid mass of 26 x 24 cm occupying whole abdomen covered with torturous dilated serpentine vessels derived from omentum. The mass was arising from the fundus of bulky uterus with small pedicle suggesting suserosal pedunculated leiomyoma. Myomectomy with infracolic omentectomy with round ligament plication was done and her post operative recovery was smooth. Histological examination confirmed it as leiomyoma. Keywords: Omentum, Pedunculated Leiomyoma, Serpentine